Advances in X-ray radiography for the measurement of dynamic effects in structured packings - Eder, Stefan; Linder, T.; Wehrli, M.; Thommes, Matthias (Chemical Engineering Science, 2023)
Imaging techniques have significantly improved the understanding of fluid dynamics in mass transfer columns over the last decades. In order to detect small-scale and highly dynamic flow phenomena such as droplets, a high spatial and temporal resolution is of crucial importance. One approach is ultrafast electron beam X-ray computed tomography, another is to extend the X-ray computed tomography by a radiographic measuring method. The latter allows a very high spatial and temporal resolution. For example, the X-ray computed tomograph used in the present study allows up to 500 projections per second. This enables the precise detection of highly dynamical effects in the entire column without influencing the flow. A new evaluation routine for radiographic measurements is presented and validated. The procedure enables to measure the liquid hold-up over a wide range with considerable low evaluation times, thus enabling a high experimental throughput. Additionally, a novel method to extract and quantify the dynamic share of the total hold-up is introduced. The possibilities arising from this are then explored utilizing Sulzeŕs structured packing MellapakTM as an example. We compare our findings of the hold-up with published data and discuss how the highly dynamic phenomena affect total flow, its local distribution, and substance dependency. Furthermore, the observations serve as indicator to which extend the computer tomographic method is suited to assess the total hold-up within a structured packing.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Distillation; Dynamic effects; Radiography; Structured packing